A novel waterproof, fast setting and high early strength repair material derived from metakaolin geopolymer. (15th October 2016) - Duan, Ping; Yan, Chunjie; Luo, Wenjun
Highlights: A novel waterproof, fast setting geopolymer repair material was proposed. Contact angle reaches 122° and specimen floats on water level after modification. The newly repair material has short setting time of 24 min and high flow of 212 mm. Compressive strength and bond strength reach 10 MPa and 0.6 MPa at 3 h, respectively. Abstract: In this work, a novel waterproof, fast setting geopolymer repair material with hydrophobic surface and high compressive strength and bonding strength was proposed. The experimental results showed that surface hydrophobic modification was completely achieved due to the increasing contact angle on the surface of geopolymer from 21° to 122°, the floating of specimens on the water surface and low water adsorption of about 0.5% after 28 days of exposure. This newly developed geopolymer repair material has short setting time of 24 min, high flow of 212 mm and high early compressive strength and bonding strength of the interfacial bonding zone as indicated by the dense microstructure.